Impressão 3D: uma alternativa para fabricação de dispositivos analíticos miniaturizados - Duarte, Lucas da Costa (2016)
This study describes the assembly and use of a RepRap 3D printer with a modeling technology fused deposition modeling (FDM) for manufacturing microfluidic devices for direct spray ionization mass spectrometry (DS-MS) assisted by paper tip as well as for generation of droplets of water/oil with integrated electrochemical detection. The low-cost 3D printer has been properly assembled and calibrated by means of pieces of kit purchased commercially. The smaller channel width obtained which allowed the uniformity 3D printing without any obstruction was 400 μm. For studies of DS-MS were used microfluidic devices consisting of a single channel (the dimensions 30 mm × 0.5 mm × 0.5 mm) connected to a sample reservoir with 3 mm diameter with low cost (R$ 0.20) and time printing (20 min). A tip paper (5 mm × 0.5 mm) was cut out and inserted at the end of the printed channel to facilitate the formation of the spray. The spraying was promoted by the application of 4 kV in the sample reservoir containing 0.1% formic acid in methanol prepared. This organic medium showed high compatibility with the polymeric material used for the printing of microfluidic chips. Using a glucose solution as a template, the spray formed by the proposed microfluidic device was extremely stable compared to the spray generated by conventional paper devices for at least 10 min. The analytical devices for viability of the printed DS-MS was successfully demonstrated by qualitative analysis of ball pens inks, caffeine, xylose and lysozyme. The DS-MS devices exhibited significant repeatability and reproducibility, making it possible to reuse. For the generation of droplets of oil/water it was built with a device channel in the T-junction configuration with 0.75 mm × 50.0 mm × 0.7 mm and containing two integrated electrodes (1.5 mm × 2.0 mm and spacing 0.5 mm) in antiparallel arrangement. These electrodes consisting of a mixture of ABS and carbon nanotubes were used for conductivity detection capacitively coupled contact (C4D). The droplets were generated by varying the flow rate of continuous phase comprised of oil + Span80/water + Triton between 10 to 60 μL/min. Through the printed electrodes it was possible to employ the system C4D system to detect the droplets generated with a satisfactory response. The intensity and width of peaks obtained exponentially decrease the extent that it increases the flow of the continuous phase. Moreover, it was possible to correlate the length of the droplet generated from the signals obtained with C4D, indicating potential as a new technique for droplet measures. Finally, the 3D printer made possible the manufacture of parts contributed to other works in cooperation to include the construction of an electrochemical cell for by batch injection analysis, a support for Snitrosothiols decomposition, a cover for conductivity detection cell, micromixers, devices for ELISA assays and mold for manufacturing zones for colorimetric analysis.